Nutritional Composition and Antimicrobial Activity of Fractionated Extracts of Garcinia kola Heckel - Daramo, B.; Adegokea, G. O. (Biological Sciences - PJSIR, 2007)
. Seeds of Garcinia kola were analysed for mi n era l and ami no acid composition . Sol vent extract i on an d fraction ati on of bioacti vc component s of th e seeds were accompl i sh ed u sing Soxh l ct ex t ractor and vacuum l iq ui d chromatograph y, re pective l y. Fraction ated extracts w ere asse sed for sen sory and antim icrobi al acti v i t i es. The seed contai n ed varyi n g amoun ts of mi cro n ut,·i cnts w i th l ow amou nt s of anti -n u tri tion a l clements. A mi n o acid s fou n d at con sid era b l e q u a nti ti es i n the seed of Garcinia kola were ess nt i a l amino acid s l i k e L- l ysi n e, L-hi stidi n e , L-argi n i n e, L-val i n e, L-meth i on i n e, L-i oleuci ne, L-l cuci n e a n d L-pheny l a l an i ne . Fractionatio n of th e da rk brown - bi tte r crud e extra ct yi el ded som e fra ct i on s (F, F5) th at w ere yellow i n col our wi t h n on -bi tte r taste. Th e fracti onated ex trac ts ex h i bit ed a nti m i crob i a l activ i t ies. Th i.: 4 most potent fract ion (F ) h ad mi n i m um i nh i bi tory con centration s of I µ glml on each of the organ i sms, Bacillus cereus, Strep tococcusfaeca lis, Candida a/bicans and mi nimu m in h i bitory con centration s (µg/ ml) of 0. 1 25, 0.5, 2 on Escherichia coli, K leb iella pn eumoniae and Stap hylococcus aureus, respecti ve l y. Th e fracti on ated ex tracts can be ex pl oi ted to preserve food systems from u ndesi rabl e acti vi ties of microorgan i sms.